Molecular mechanism of antimutagenicity by an ethoxy-substituted phylloquinone (vitamin K1 derivative) from spinach (Spinacea oleracea L.). (1st October 2020) - Kumar, Sanjeev; Tripathi, Jyoti; Srivastava, Ashish K.; Gautam, Satyendra
Abstract: In our previous study, an antimutagenic compound from spinach ( Spinacea oleracea L.), ethoxy-substituted phylloquinone (ESP) was isolated and characterized. The current study deals with elucidation of the possible mechanism of antimutagenicity of ESP against ethyl methanesulfonate (EMS) deploying model systems such as human lymphoblast (TK +/- or TK6) cell line (thymidine kinase gene mutation assay) and Escherichia coli MG1655 (rifampicin resistance assay). Findings of the study ruled out the possibility of direct inactivation of EMS by ESP. DAPI competitive binding assay indicated the DNA minor groove binding activity of ESP. Interestingly, ESP did not display major groove binding or intercalating abilities. Further, proteomics study using 2-D gel electrophoresis in E. coli and subsequent studies involving single gene knockout strains revealed the possible role of tnaA (tryptophanase) and dgcP (diguanylate cyclase) genes in observed antimutagenicity. These genes have been reported to be involved in indole and cyclic-di-GMP biosynthesis, respectively, which eventually lead to cell division inhibition. In case of TK +/- cell line system, ADCY genes (adenylate cyclase), a functional analogue of dgcP gene, were found to be transcriptionally up-regulated. The generation/doubling time were significantly higher in E. coli or TK +/- cells treated with ESP than control cells. The findings indicated inhibition of cell proliferation by ESP through gene regulation as a possible mechanism of antimutagenicity across the biological system. Cell division inhibition actually provides additional time for the repair of damaged DNA leading to antimutagenicity. Graphical abstract: Image 1 Highlights: Ethoxyl-substituted phylloquinone (ESP) displayed strong antimutagenic potential. ESP interacted with minor groove of DNA. Proteomics analysis indicated up-regulation of genes inhibiting cell proliferation. This inhibition provided additional time for repair of damaged DNA. ESP worked through bio-antimutagenic mechanism.